Importance of stability and retention of double total prostheses: factors related to its use in the etiology of temporomandibular disorders - Renhe, Letícia de Souza; Miranda, Jean Soares; Malta, Natália Veloso; Gonçalves Leite, Isabel cristina; Pereira Leite, Fabiola Pêssoa (Brazilian Dental Science, 2016)
Objective: Evaluate the prevalence of Temporomandibular Disorder in patients with full double prosthesis. Material and Methods: The sample was composed of 40 volunteer patients, aged between 34 and 92 years, with upper and lower dentures, assisted at the Total Prosthodontics Clinic of the School of Dentistry at the Federal University of Juiz de Fora. Patients were evaluated by a single trained examiner and the diagnosis of TMD was established from the axis I of the RDC/TMD. Results: The prevalence of TMD in the sample was 42.5%, and most patients were female. Although there was no statistical significance between the time of use of the prosthesis and the presence of TMD was found, there was a correlation between time without use of prosthesis and the presence of disc displacement. Conclusion: According to the methodology applied and the results of this study, it can be concluded that there was a considerable prevalence of TMD in patients with double dentures, but there was no correlation between the use of full and DTM prosthesis.Keywords: Facial Pain; Temporomandibular Joint Dysfunction Syndrome; Complete Denture.